Identifikasi Perkembangan Aspek Emosi, Moral, Kepribadian, Sosial, Bahasa, Fisik, Kognitif, dan Motorik Terhadap Siswa Sekolah Dasar - Putri, Ajeng Adistya; Tsania, Aura Rizky; Liandi, Nura Alisha; Syahroni, Rendi Herman; Hermayanti, Risa Aulia; Handayani, Shinta Risma; Mufidah, Siti Rahma; Wati, Talitha Arista (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this research is to identify the development of emotional, moral, personality, social, language, physical, cognitive, and motor aspects of elementary school students. This research was carried out by observation and direct observation methods on 23 5th grade students of SDN 068 Sindanglaya. This research was carried out through a qualitative descriptive method. The instruments used in data collection are observation and interviews. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. The results of the study showed that in the language aspect, speaking ability reached 100%, reading, listening, and communication 80% each. The emotional aspect shows all indicators at 60%. The moral aspect stands out in responsibility (100%), while empathy and honesty 60%. The personality of students also needs to be improved with all indicators at 60%. In the physical aspect, sports while playing reached 100%. The motor aspect, locomotor reaches 90%, non-locomotor and manipulative 80%. Social aspects, social interaction 90%, others 80%. Cognitive aspects, thinking ability 90%, and others 80%. It can be concluded that students show good abilities in various aspects.